2020
DOI: 10.4028/www.scientific.net/kem.860.160
|View full text |Cite
|
Sign up to set email alerts
|

Study of Purity and Electrical Resistivity of Eu<sub>1.91</sub>Ce<sub>0.09</sub>CuO<sub>4</sub> and Eu<sub>1.84</sub>Ce<sub>0.16</sub>CuO<sub>4</sub>

Abstract: The samples of Eu2-xCexCuO4 (ECCO) with x = 0.09 (Eu1.91Ce0.09CuO4) and x = 0.16 (Eu1.84Ce0.16CuO4) have been synthesized by the solid reaction method without annealing. Each sample is covered with CuO to prevent excess oxygen entering the sample. The purity and electrical resistivity were investigated by x-ray Diffraction (XRD) and resistivity measurements. From the XRD analysis, it was found that the purity of ECCO phase was 93.5% with tetragonal structure of T’ for x = 0.09 while 96.1% for x = 0.16. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Puncak utama struktur kristal tetragonal T' yang umum ditemukan pada system superkonduktor doping elektron pada indeks Miller (103) dan (110) ditunjukkan pada Gambar 1(c-d). Hasil ini menunjukkan bahwa proses sintesis telah berhasil dilakukan dengan mendapatkan struktur kristal yang sesuai dengan literatur [4][5][6][7][8][9][10][11]. Gejala superkonduktivitas umumnya dapat ditentukan dengan adanya interaksi atom pada lapisan konduksi yang berasal dari charge reservoir.…”
Section: Hasil Dan Pembahasanunclassified
“…Puncak utama struktur kristal tetragonal T' yang umum ditemukan pada system superkonduktor doping elektron pada indeks Miller (103) dan (110) ditunjukkan pada Gambar 1(c-d). Hasil ini menunjukkan bahwa proses sintesis telah berhasil dilakukan dengan mendapatkan struktur kristal yang sesuai dengan literatur [4][5][6][7][8][9][10][11]. Gejala superkonduktivitas umumnya dapat ditentukan dengan adanya interaksi atom pada lapisan konduksi yang berasal dari charge reservoir.…”
Section: Hasil Dan Pembahasanunclassified
“…In our previous study, it was found that Eu 2– x Ce x CuO 4+α–δ exhibited a bad metal when x = 0.09, 0.15, and 0.16 in the normal state, indicating an increase in resistivity. 11 , 12 Here, we expand the Ce concentration of Eu 2– x Ce x CuO 4+α–δ from an underdoped regime to an overdoped regime to study the electrical properties in the normal state. The Arrhenius law and Mott’s variable range hopping (VRH) model were used for analyzing the carrier transport mechanism.…”
Section: Introductionmentioning
confidence: 99%